2019
DOI: 10.1111/liv.14297
|View full text |Cite
|
Sign up to set email alerts
|

Oral glutamine challenge is a marker of altered ammonia metabolism and predicts the risk of hepatic encephalopathy

Abstract: Background The current therapies for hepatic encephalopathy (HE) are not completely effective in all patients, probably due to the physiopathological heterogeneity and the different conditions underlying the bout of HE. We hypothesized that oral glutamine challenge (OGC) is able to predict the risk of HE through the identification of various features and types of HE. Methods We included 238 cirrhotic patients (198 without and 40 with a previous HE episode) that underwent OGC, obtaining baseline and 60 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…and ours are not easily comparable given that except for PHES different testing strategies were used to define MHE. Moreover, our current study cannot answer whether the predictive ability of a combination of PHES and S‐ANT1 is better for predicting OHE episodes than a combination of PHES and, for example, an oral glutamine challenge or even genetic risk scores [31, 32]. Additionally, we acknowledge that results in S‐ANT1 were only available for a subset of the cohort; therefore, our findings need validation in future prospective studies.…”
Section: Discussionmentioning
confidence: 87%
“…and ours are not easily comparable given that except for PHES different testing strategies were used to define MHE. Moreover, our current study cannot answer whether the predictive ability of a combination of PHES and S‐ANT1 is better for predicting OHE episodes than a combination of PHES and, for example, an oral glutamine challenge or even genetic risk scores [31, 32]. Additionally, we acknowledge that results in S‐ANT1 were only available for a subset of the cohort; therefore, our findings need validation in future prospective studies.…”
Section: Discussionmentioning
confidence: 87%
“…[173][174][175] Importantly, a response to intervention that is associated with a reduction in ammonia concentrations is associated with good outcomes, 41,176 while the reverse is true if ammonia increases further. 49,177 This observation is supported by studies of various interventions such as lactulose, rifaximin or extracorporeal albumin dialysis where reduction in ammonia was indeed associated with improvement in the severity of HE. 31,178,179 In a prospective study, an ammonia cutoff of 80 lmol/L was shown to be associated with a high risk of death, irrespective of the severity of HE.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 79%
“…3,4,97,98,[172][173][174] Notably, most studies excluded patients with a history of recurrent overt HE. Patient factors for the development of post-TIPS overt HE includes prior HE, advanced liver dysfunction (CTP class C, MELD score >18), 4,97,98,175,176 older age, 166 increased creatinine level, 166 hyponatremia, and sarcopenia. 177,178 Question 2.…”
Section: Cardiopulmonary Renal and Neurologic Considerations In Transjugular Intrahepatic Portosystemic Shuntmentioning
confidence: 99%
“…174 Few studies have determined the role of oral glutamine challenge in prognostication for overt HE after TIPS. [175][176][177] Cognitive testing by and large worsens after TIPS, which can contribute to further worsening of health-related quality of life. 162,178 In patients being considered for elective TIPS, a diagnosis of covert HE should guide discussion of the pros and cons of TIPS creation with patients, family members, and clinical teams.…”
Section: Q32mentioning
confidence: 99%